Redescription of the Korean sandlance Hypoptychus dybowskii from Korea - Hyuck Joon Kwun; Mi-Jin Yim (Fisheries and Aquatic Sciences, 2018)
Abstract Hypoptychus dybowskii, the Korean sandlance, is widespread in cold areas of the North Pacific. Although H. dybowskii has been considered to occur on the coast of Hamgyeongnam-do in Korea, the species is also distributed along the coast of Goseong-gun, Gangwon-do, south of Hamgyeongnam-do in the eastern part of the Korean Peninsula on the basis of newly collected specimens. In addition, many Koreans confuse H. dybowskii and Ammodytes japonicus (= A. personatus for Korean specimens) because the Korean common name or dialect of both species is “Yang-mi-ri”, yet the two species differ in their external morphology. Hypoptychus dybowskii differs from A. japonicus in the location of the origin of the dorsal fin and the number of dorsal and anal fin rays.